The future of university or universities of the future: a paradox for uncertain times. Issue 7 (26th March 2020) - Alexander, Allen; Manolchev, Constantine
Abstract : Purpose: Using narratives from leading international academics and commentators, the authors chart four, possible, "universities of the future" models and discuss how current university management issues can enable or hinder them. Design/methodology/approach: Deploying a Gioia methodology analysis of "University of the Future" narratives, the authors derive 12 categories of institutional properties and, ultimately, four distinct models. Findings: The authors identify how current, classic and polytechnic institutions can adapt their operations and service delivery in order to transition into future-ready business models. Originality/value: The authors interpret the opinions and predictions from world-leading experts in the higher education field in order to present the first, to our knowledge, typology of aspirational university models.